OpenGL® SuperBible, Third Edition - Wright, Richard; Lipchak, Benjamin (Sams, 2004)
In a world where everything from how we take pictures to how we get our food is designed to happen as quickly and easily as possible, it can take a lot longer to learn how to make it all work behind the scenes. Theories and concepts can weigh you down when all you really want to know is how to create, design and go. That's where OpenGL SuperBible comes inches Complete with supporting figures and a CD packed with free tools, demos and libraries, OpenGL SuperBible simplifies 3D programming concepts without wasting your time with programming theory. Mac and Windows users will both find this comprehensive hands-on guide helpful as you learn to program for games, visualization applications and multi-platforms. This is the ultimate resource for any new programmer.
Keywords: Augmented reality; Virtual reality; Three-dimensional imaging; Computer graphics; Virtual Reality; Imaging, Three-Dimensional; Computer Graphics; Réalité augmentée; Réalité virtuelle; Imagerie tridimensionnelle; Infographie; augmented reality; virtual reality; three-dimensional; computer graphics